RAHASIA MULTIPLE INTELLIGENCE PADA ANAK - Juli Astuti (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2018)
In educational institutions, parents, teachers and the public often assume that intelligence can only be seen through academic scores and formal test results such as getting a high score or being ranked in a class. This conception is outdated and superficial. In this era of globalization where educational practitioners are exploring the concept of Multiple Intelligences. Multiple Intelligences as a broad concept of intelligence and has undergone several changes due to the emergence of the theory of multiple intelligences proposed by a psychologist from Harvard University. Intelligence is not limited to formal tests, it's a multidimensional and one's discovery process of competence. Multiple Intelligences is a theory of intelligence pioneered by a psychologist from Harvard University who shows that everyone is intelligent and tends to have intelligence among the ten dimensions of intelligence. In Islam (al Qur'an) multiple intelligences is actually already put forward various developments about intelligence and various human potential. There are ten dimensions of intelligence put forward by Hardward Gardner namely linguistic intelligence, logical-mathematical intelligence, visual-spatial intelligence, kinesthetic-physical-kinesthetic, musical intelligence, interpersonal intelligence, intrapersonal intelligence, naturalistic, existential and emotional intelligence